The effect of ELSA Speak Application Towards Students’ Speaking Skill at the Eighth Grade of SMPN 4 Cijaku Lebak-Banten in the Academic Year 2023/2024 - Putri, Anes Indriali; Rohimajaya, Nur Azmi; Munawaroh, Tatu (CV. Kurnia Grup, 2024)
This research aims to determine the significant effect of the ELSA Speak Application towards Students’ Speaking Skill in the Eight Grade of SMPN 4 Cijaku Lebak-Banten Academic Year 2023/2024. This research paper used a quantitative approach and quasi-experimental design.This research was conducted in Mei-Juni, and the researcher chose two classes, namely the control class and the experimental class. The sample selection technique is purposive sampling; the researcher used class VIII A (27 students) as the experimental class and class VIII B (27 students) as the control class. The experimental group was taught using the ELSA Speak Application, while the control group was taught using the Cake English Learning Application. In the data collection technique, the researcher gave a pre test and post test. The control group’s pre-test mean was 56,6 and the experimental groups’ 57,2. Then the control group s’ post-test mean was 70,7 and the experimental groups’ post-test mean was 74,8. In analyzing the data, the researcher use SPSS 22 statistical calculations and post-test result of control and experimental classes to analyze hypothesis testing. Researcher found two -sided significant result = 0.000 < ꭤ 0.05. Therefore, the researcher concluded that the use of the ELSA Speak Application had a significant impact on students’ speaking skill at SMPN 4 Cijaku Lebak-Banten.